Mass gatherings and public health: the experience of the Athens 2004 Olympic Games (World Health Organization. Regional Office for Europe, 2007)
Large-scale mass gatherings, such as the Olympic Games, represent significant challenges for the entire health sector of host countries. Emerging global public health threats of natural or deliberate nature increase considerably the health and safety vulnerability of mass gatherings. Major areas of public health responsibility include health care capacity and mass-casualty preparedness; disease surveillance and outbreak response; environmental health and food safety; public information and health promotion; public health preparedness and response to incidents potentially involving the deliberate use of explosives, biological and chemical agents or radionuclear material; and leadership, operations and unified command. This book comprehensively and systematically presents the experience of and lessons learned from the public health aspects of the preparations and conduct of the Athens 2004 Olympic Games. Documenting this experience can be a source of valuable information and knowledge for governments at all levels and communities in building their capacity for not only large-scale events but also preparing to deal with the avian influenza pandemic threat or other emergencies such as flooding and phenomena often associated with climate change.